2005
DOI: 10.1176/appi.ajp.162.5.867
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Disorder in Clinical Practice

Abstract: Borderline personality disorder patients in research samples are highly similar to those seen in a cross-section of clinical practice. However, several studies have now replicated a portrait of borderline personality disorder symptoms that places greater weight than the DSM-IV description on the intense psychological pain of these patients and suggests candidate diagnostic criteria for DSM-V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 49 publications
5
75
0
Order By: Relevance
“…From another point of view, this heterogeneity might be related to the lack of coherence of the BPD diagnosis. In other words, BPD diagnosis is associated with a heterogeneous spectrum of clinical presentations, and much research has suggested the existence of different BPD patients subtypes [37,38,39]. In the future, it would be interesting to examine the relationship between these BPD subtypes and the activation of different relational patterns in psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…From another point of view, this heterogeneity might be related to the lack of coherence of the BPD diagnosis. In other words, BPD diagnosis is associated with a heterogeneous spectrum of clinical presentations, and much research has suggested the existence of different BPD patients subtypes [37,38,39]. In the future, it would be interesting to examine the relationship between these BPD subtypes and the activation of different relational patterns in psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Data on inpatient hospitalization and outpatient sessions from therapists were obtained from a questionnaire adapted from Zittel Conklin and Westen (2005) administered at three time points within the 30-month duration of the TOP DD study, including follow-ups at month six (T2), month 18 (T3), and month 30 (T4). Data from patients on their inpatient hospitalization days was obtained from a questionnaire adapted from the National Health and Nutrition Examination Survey (National Center for Health Statistics, n.d.) administered at four time points within the 30-month study, including at baseline (T1) as well as the three follow-ups (T2–T4).…”
Section: Methodsmentioning
confidence: 99%
“…Externalization of the alien self is desirable for the child with a disorganized attachment but is a matter of life and death for a traumatized individual who has internalized the abuser as part of the self. The unbearable emotional experience can include feeling abandoned, evil, misunderstood, victimized, inferior, and monstrous (Bradley & Westen, 2005;Zanarini, Frankenburg, Hennen, & Silk, 2003;Zittel Conklin & Westen, 2005). The externalization of these internal states is widely recognized in the common counter-transferential reactions of therapists working with borderline patients -anger and hatred, helplessness and worthlessness, fear and worry, resentment, and urges to save and rescue the patient (Gabbard & Wilkinson, 1994).…”
Section: (C) Re-externalization Of the Alien Selfmentioning
confidence: 99%